A non‐destructive approach to collect nest material data using photographs. (6th May 2021) - Sugasawa, Shoko; Edwards, Sophie C; Stanforth, Rowan; Bruton, Emily; Hansell, Mike; Reilly, Maggie; Healy, Susan D
Abstract : The materials that birds use to build their nests have a profound effect on nest quality and consequently on the builder's reproductive success. Given that the common method to quantify nest materials by dismantling nests takes time and limits study species, we developed a non‐destructive and much quicker method for quantifying nest materials using nest photographs. Using our photographic method, the proportions of the main materials in 45 Blue Tit Cyanistes caeruleus and 20 Dartford Warbler Sylvia undata nests, including grass, heather and moss, matched those found by dismantling the nests, but the proportions of rarer animal‐derived materials differed between the two methods. Provided that there is an initial calibration with the dismantling method, the photographic method offers two key advantages: a reduction in the time it takes to quantify the major components of nests, and application to previously inaccessible data, including museum collections. Together, these advantages encourage further study of nesting materials and enable a better understanding of avian nest diversification.